Identification of YPL014W (Cip1) as a novel negative regulator of cyclin‐dependent kinase in Saccharomyces cerevisiae. (23rd March 2016) - Ren, Ping; Malik, Asrar; Zeng, Fanli
Abstract : Cyclin‐dependent kinases drive cell division cycle progression in eukaryotic cells. In the model eukaryotic organism Saccharomyces cerevisiae (budding yeast), a single cyclin‐dependent kinase, Cdk1, is essential and sufficient to drive the cell cycle. Misregulated CDK activity induces unscheduled proliferation as well as genomic instability, which are hallmarks of the cancer. Here, we report a novel Cdk1‐interacting protein, YPL014W, which we name Cip1 (for Cdk1‐interacting protein 1). Our results show that Cip1 specifically interacts with G1 /S‐phase Cln2–Cdk1 complex but not with S‐phase Clb5–Cdk1 or M‐phase Clb2–Cdk1 complexes. Also Cip1 phosphorylation is cell cycle regulated in a S‐phase Cdk1‐dependent manner. Over‐expression of Cip1 blocks cell cycle progression in G1 and stabilizes the S‐phase Cdk1 inhibitor Sic1 in vivo . In addition, disruption of CIP1 ( cip1 Δ) leads to faster G1 /S‐phase transition compared to wild‐type cells. Moreover, Cip1 inhibits Cln2–CDK activity both in vivo and in vitro . Our finding proves Cip1 as a novel negative regulator of cyclin‐dependent kinase in S. cerevisiae . Abstract : We report a novel Cdk1‐interacting protein, YPL014W, which we name Cip1 (for Cdk1‐interacting protein 1). Cip1 directly interacts and inhibits Cln2–CDK activity both in vivo and in vitro . Our finding proves Cip1 as a novel negative regulator of cyclin‐dependent kinase in S. cerevisiae .